Assessing effectiveness of nurture groups in Northern Scotland. Issue 3 (4th September 2013) - Shaver, Isabel; McClatchey, Kirstie
Abstract : The aim of this small‐scale study was to assess the effectiveness of nurture groups in Northern Scotland. Data were collected from children ( N  = 19) and staff ( N  = 5) from three nurture groups. Pre‐ and post‐nurture group Boxall Profile information was also assessed for 33 children across two of the nurture groups. Analysis of the Boxall Profiles found that nurture group children had made significant gains. The majority of children reported that they feel happy and enjoy attending the nurture groups. Nurture group staff reported improvements in the children, and that parents are positive about the nurture groups. However, staff did report a number of challenges that the nurture group face. Overall, this study contributes to the evidence that nurture groups can be an effective intervention for improving social, emotional and behavioural outcomes for children.